The Policy of Changing Street Names to Betawi Cultural Figures in DKI From a Deliberative Policy Perspective: Study Mpok Nori street - Ismowati, Mary; Sujono, Sujono; Balqis, Silvia; Adawiyah, Aiga (Iapa Proceedings Conference, 2024)
This research explores the policy of changing the name of Bambu Apus Street to Mpok Nori Street in Jakarta from a deliberative policy perspective. Deliberative policy is a decision-making process that involves discussion between the government and the affected community. However, this research found that the policy was not implemented in a deliberative manner. The community was not involved in prior consultations or discussions. There was minimal socialization, and residents only became aware of the name change after the policy was implemented. This research employs a qualitative approach with purposive sampling interviews as the main method. The data indicates that the change of this street name was taken top-down by the government without adequate public consultation, resulting in dissatisfaction among the affected community. Additionally, the name change was not accompanied by direct adjustments to population documents, requiring individuals to gradually update their data. In conclusion, the policy of changing street names is not in line with the ideal principles of deliberative policy. This has resulted in low public support for the street name change, highlighting the importance of public involvement in the policy-making process.